Evaluation of Planning, Design, and Implementation of Wastewater Treatment Plant (WWTP) on Reservoirs Project in DKI Jakarta : (Case Study: Aseni, Batu Bangkong, Bambu Hitam) - Rahayu, Mayang Manguri; Andriani, Tetty; Machrunnisa; Marsudi, Sidik (Global Writing Academica Researching & Publishing, 2025)
Wastewater Treatment Plants (WWTPs) play a crucial role in maintaining water quality in water infrastructure such as reservoirs and retention ponds, especially in urban areas experiencing high environmental pressures. This study evaluates the completeness of WWTP design documents, the technical suitability of planning, and the environmental risks of three water infrastructure projects in Jakarta: Aseni Reservoir, Bambu Hitam Reservoir, and Batu Bangkong Reservoir. The methods include technical document auditing (DED, RKS, technical specifications, BOQ), field inspections, and analysis of national regulations (Ministerial Regulation LHK No. 68/2016, PUPR No. 4/2017, and national standards). Results show significant nonconformities, including the absence of detailed WWTP process units, incomplete mechanical–electrical specifications, lack of commissioning procedures, and weak integration of WWTP components in contractual documents. Field observations also reveal potential increases in pollution loads due to suboptimal inlet–outlet conditions and the absence of a pre-integrated WWTP system. This study emphasizes the importance of revising planning documents, standardizing WWTP design, and applying proper commissioning and environmental monitoring procedures.